Urban expansion and the formation of technogenic deposits in tropical areas: The case of Araguaína city - Machado, Carlos Augusto (Investigaciones Geográficas: Una mirada desde el sur, 2014)
Technogenic deposits are formed with the materials produced by the human activity and direct or indirect deposition of sediments resulting in artificial bodies with an own dynamic in each environment. Among the problems, the formation and expansion of the technogenic deposits in the Araguaína city, north of Tocantins state (Brazil), may be subject to the economic cycles and technogenic resources in the last decades. The present study aims at two main aspects, at first a short discussion about the technogenic deposits worldwide will be made and then our aim will be analyzing will be made about the different types of inorganic, chemical, organic and terrigenous deposits in different environments: terrestrial, fluvial and lagoon. The applied methodology was based on the review of the literature, characterization of the study area and urban expansion, identification of satellite images and the structural and morphologic characterization of the technogenic materials. The results point at the link between the types of materials and phases of urban expansion, which mean that the deposits have a higher concentration of organic material and dominance of inorganic materials. Due to the necessity of adjusting the relief and soil for the construction, some areas suffered severe topographic changes and great deposition of technogenic materials. The future perspectives, based on the present conditions, indicate an increasing number and variety of technogenic deposits in some study areas